2020
DOI: 10.1101/2020.01.06.889998
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial accumulation of salicylic acid is regulated by RBOHD in potato immunity against viruses

Abstract: Corresponding author: Tjaša Lukan (tjasa.lukan@nib.si). SIGNIFICANCETo get towards sustainable resistance in the field, it is important to understand mechanisms of immune signaling. We here show novel aspects of spatial regulation in effector-triggered immunity (ETI) against potato virus Y. A detailed spatiotemporal analysis in and surrounding the foci of viral infection, on ultrastructural, biochemical and gene expression levels revealed that redox state maintenance is tightly spatiotemporally regulated. We a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Early induction of photosynthesis-related genes, that could be related to increased energy demands for efficient defense response, was observed in HR of potato with PVY [58,65] (Figure 2). Similarly, granule bound starch synthase gene was induced only in the tissue surrounding viral foci in incompatible interaction [20].…”
Section: Hypersensitive Response-mediated Resistance: Response At Thementioning
confidence: 99%
See 4 more Smart Citations
“…Early induction of photosynthesis-related genes, that could be related to increased energy demands for efficient defense response, was observed in HR of potato with PVY [58,65] (Figure 2). Similarly, granule bound starch synthase gene was induced only in the tissue surrounding viral foci in incompatible interaction [20].…”
Section: Hypersensitive Response-mediated Resistance: Response At Thementioning
confidence: 99%
“…Rywal, detection of large amounts of hydrogen peroxide and upregulation of several genes involved in redox state regulation from 1 day post-inoculation (dpi) indicated the importance of ROS signalling in an efficient HR ( [58], Figure 2). Recent spatiotemporal analysis of responses in and surrounding the foci of viral infection, on ultrastructural, biochemical, and gene expression levels revealed that tight spatiotemporal regulation of redox state maintenance is required for the successful arrest of the virus [20]. Respiratory Burst Oxidase Homolog D (RBOHD) regulates spatial distribution of SA accumulation and is indispensable for viral arrest [20].…”
Section: Hypersensitive Response-mediated Resistance: Response At Thementioning
confidence: 99%
See 3 more Smart Citations